Organizational support: Mechanisms to affect perceived overqualification on turnover intentions: a study of Chinese repatriates in multinational enterprises. Issue 7 (6th November 2017) - Ye, Xiaoqian; Li, Ling; Tan, Xuejun
Abstract : Purpose: Drawing on recent literature and empirical data, the purpose of this paper is to explore the relationships between perceived organizational support (POS), perceived overqualification (POQ) and turnover intentions (TI) in repatriates working in multinational corporations (MNCs). Design/methodology/approach: Survey data were collected from 145 repatriates who had been contacted beforehand from MNCs in China. Structural equation modeling and hierarchical regression are used to examine the data. Findings: It is shown that POQ and POS both affect repatriates TI, with POQ having the stronger effect, while POS plays a mediatory role between POQ and TI. Specifically, under the same POQ, repatriates TI will decrease as the POS increases. Research limitations/implications: The study design is cross-sectional and based on self-reporting, which makes causal explanations of the results difficult. Practical implications: POQ and POS are both shown to influence TI, with POQ having the greater effect. This means managers can offset the effect of repatriates POQ on TI by providing better support and assistance, which can help MNCs reduce repatriates TI and retain employees. Originality/value: This paper examines the antecedents of TI, and adds valuable new insights to the literature on repatriation through its research data, offering further evidence that managers in transnational corporations should pay more attention to organizational support policy on repatriates in order to reduce their turnover.